Reaction of common bean lines to Xanthomonas axonopodis pv. phaseoli and Curtobacterium flaccumfaciens pv. Flaccumfaciens - Ribeiro,Tamires (2017)
Abstract The aim of this study was to evaluate the resistance of 58 common bean lines against common bacterial blight (Xanthomonas axonopodis pv. phaseoli) and bacterial wilt (Curtobacterium flaccumfaciens pv. flaccumfaciens). The experimental design consisted of completely randomized blocks, with four replications per pathogen. The results were subjected to variance analysis by the F test at 1% probability. Significant differences between the treatments indicated different resistance levels among the lines against both pathogens. According to the Scott-Knott test, six lines were resistant to Xanthomonas axonopodis pv. phaseoli, 14 moderately resistant, and 38 susceptible. To Curtobacterium flaccumfaciens pv. flaccumfaciens, 11 lines were resistant, 26 moderately resistant and 21 susceptible. Among these, the lines Pr10-3-4/1, Pr10-5-2/1 and Pr10-5-2/2 of the black bean group and C10-2-4/2 of the Carioca group were resistant to both major bacterial diseases affecting common bean in Brazil.